2016
DOI: 10.5539/gjhs.v9n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Obstetricians and Gynecologists in Teleconsultation with Medical Residents: A Qualitative Study

Abstract: Objective: To explore the experiences of specialists, residents, and experienced personnel of obstetrics and gynecology regarding telephone consultation by specialized residents and on-call experts Design: Qualitative study based on inductive content analysis.Setting: Three departments of obstetrics and gynecology, affiliated to Mashhad University of Medical Sciences, Mashhad, Iran.Population: A purposive sample of 16 specialists, residents and experienced staff.Methods: Eighteen semi-structured interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The qualitative study has shown that specialists during teleconsultation with residents faced significant challenges at the time of the diagnosis and treatment of patients; the majority of these problems were caused by insufficient confidence in the judgment of the resident or disproportionate volume of information received concerning the patients [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative study has shown that specialists during teleconsultation with residents faced significant challenges at the time of the diagnosis and treatment of patients; the majority of these problems were caused by insufficient confidence in the judgment of the resident or disproportionate volume of information received concerning the patients [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our educational hospitals and in the absence of clinical experts (eg, holidays), the senior and junior residents are responsible for patient care through telephone consulting with an on-call physician. Our previous study had shown that there is no formal education about the consultation process for requesting a resident, and it is learnt only by oral education or observing the performance of senior ones [ 4 ]. So, data and information content that is exchanged in these consultations has no standard format or template.…”
Section: Introductionmentioning
confidence: 99%